2018
DOI: 10.12934/jkpmhn.2018.27.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression and Suicide Attempts among South Korean Juvenile Victims of Violence: Secondary Data Analysis from the 11th Korea Youth Risk Behavior Web-based Survey

Abstract: The aim of this study was to examine factors influencing depression and suicide attempts among South Korean adolescent victims of violence. Methods: This secondary data analysis was based on the 11th (2015) Korea Youth Risk Behavior Web-based survey. The study sample comprised of 1,565 students who were victims of violence and subsequently required medical treatment during the past 12 months. Descriptive statistics and logistic regression analyses were completed. Results: Factors associated with adolescent dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, the 2018 KYRBS data analysis showed that suicide attempts were 7.38 times higher in teenagers who had been treated by a doctor due to violence [ 18 ]. According to the 2015 KYRBS data analysis, teenagers were 2.39 times more likely to commit suicide in cases of repeated violence [ 38 ], and the more multicultural teenagers suffered from school violence, the more they thought of suicide [ 39 ]. Additionally, according to the 2015 KYRBS data analysis, multicultural teenagers' experience of violence was a very significant factor in suicidal thoughts [ 32 ] and had a significant influence on both suicidal plans and suicide attempts in line with suicidal thoughts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the 2018 KYRBS data analysis showed that suicide attempts were 7.38 times higher in teenagers who had been treated by a doctor due to violence [ 18 ]. According to the 2015 KYRBS data analysis, teenagers were 2.39 times more likely to commit suicide in cases of repeated violence [ 38 ], and the more multicultural teenagers suffered from school violence, the more they thought of suicide [ 39 ]. Additionally, according to the 2015 KYRBS data analysis, multicultural teenagers' experience of violence was a very significant factor in suicidal thoughts [ 32 ] and had a significant influence on both suicidal plans and suicide attempts in line with suicidal thoughts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social support was assessed with a one-item scale ("Can you talk about your concerns with people (i.e., father, mother, brothers, sisters, friends, teachers, and others)?"). Answers were dichotomized (no = 0 and yes = 1) [36].…”
Section: Social Supportmentioning
confidence: 99%
“…The risk factors for depression in young include increased screen time (spending long hours on laptops, mobile phones, etc), bullying, limited social networking, the recent history of being physically and or sexually abused, poor academic performance, poor health, authoritative parents, alcohol abuse, positive family history of depression and drugs abuse. [6][7][8][9][10][11][12] Depression is on the rise in Pakistan. Approximately 44% of Pakistan's population is suffering from depression.…”
Section: Introductionmentioning
confidence: 99%